Description of a new moss-feeding species of Cidariplura Butler, 1879 (Lepidoptera, Erebidae) from China - Han, Hui-Lin; Tang, Liang; Wang, Min; Owada, Mamoru (Zootaxa, 2023)
A new species of Cidariplura Butler, 1879, Cidariplura guiyuea sp. n. is described from Guizhou and Guangdong Provinces, China, which was reared from larva to adult feeding on Cyrto-hypnum gratum (P. Beauv.) Buck & Crum. The new species is illustrated with images of the adult, male genitalia and compared with similar species Cidariplura bilineata (Wileman & South, 1919) and Cidariplura brevivittalis (Moore, 1867).